The manufacturing issues of technical products made of polyimide – carbon fibers composite by means injection moulding process - Frącz, Wiesław; Janowski, Grzegorz; Mikhasev, Gennadi (Advances in Mechanical and Materials Engineering, 2016)
Nowadays modern commercial simulation software provides acceptably faithful representation of reality, assuming the correctness of boundary conditions and reliability of data of processed composite material. In the case of non-standard plastics which include polyimide, we do not always have access to the target material and we do not have proper equipment to produce such products. Due to very interesting properties of the polyimide and its low popularity in use as an injection moulding material, the analysis of injection moulding of tooth plastic gear made from carbon fiber-polyimide composite was made. In this work the chosen material data, necessary for the numerical analysis, were presented. The impact analysis of main factors controlling the volumetric shrinkage during injection moulding processing was conducted. It was found that the greatest impact on the quality criterion is the melt temperature. To optimize control factors, the Taguchi orthogonal plans were used. In addition, the issue of polyimide properties, the possibility of its injection moulding and applications was discussed.